Human Capital dan Kinerja UKM: Peranan Praktik Akuntansi Manajemen sebagai Pemediasi - Rachmawati, Dyna; Tamara, Felyta (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
This study aims to examine the role of Management Accounting Practice (PAM) as a mediator in the relationship between human capital and SME performance. The study population is SMEs in the province of East Java, the sample technique using convenience sampling method. The data collection method uses e-survey via Whatapss and Line social media because it is the most popular in Indonesia. The data that was collected was 108 SMEs. Hypothesis testing uses partial least squares – structural equation modeling (PLS-SEM). The test results show that human capital has a significant and positive effect on SME performance, PAM has a significant and positive effect on SME performance, and PAM has a role as a partial mediation between PAM and SME performance. The research results have theoretical implications, namely human capital is an antecedent variable that influences the use of PAM and PAM has a role as a partial mediation. Meanwhile, the practical implication is that human capital in the context of SME owners has an important role for the survival of SMEs during a pandemic. And the use of PAM will help SMEs to be able to maintain their viability. Keywords: Covid-19 pandemic; Human Capital; Management Accounting Practices; SMEs’ Performance